Tales of mystery & imagination - Poe, Edgar Allan, 1809-1849.; Clarke, Harry (Mineola : Calla Editions, 2008)
Presents an anthology of tales of horror and the supernatural.
English Language & Literature.
Keywords: Horror tales, American; Children's stories, American; Horror stories; Short stories